Digital Literary Proficiency of 4th Semester Student at UIN Raden Mas Said Surakarta: Kemampuan Literasi Digital Mahasiswa Semester 4 UIN Raden Mas Said Surakarta - Idha Aulia Hasanah; Solikha Nur Dzulfiani; Yahya Nur Fadillah (Fakultas Adab dan Bahasa UIN Raden Mas Said Surakarta, 2025)
In today's digital world, being digitally literate is essential for university students to thrive both academically and socially. This research examines the level of digital literacy skills among 4th semester students at UIN Raden Mas Said Surakarta, using Ng’s (2012) framework, which includes the technical, cognitive, and socio-emotional aspects. A descriptive quantitative approach was used, involving a sample of 120 students from different faculties. Data were gathered through a validated questionnaire and examined using descriptive statistics. The results indicate that students have a high level of technical literacy (M = 4. 12), a moderate level of cognitive literacy (M = 3. 41), and a medium-high level of socio-emotional literacy (M = 3. 78). Although many students feel confident in using digital resources (Kirschner and De Bruyckere, 2017), there are still deficiencies in areas such as critical evaluation and digital ethics (List, 2019; Eshet- Alkalai, 2004). The study suggests that universities should incorporate digital literacy training into their curricula to better equip students with the necessary skills for the 21st century (UNESCO, 2018).